2010
DOI: 10.1016/j.otsr.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Complications of the Luque–Galveston scoliosis correction technique in paediatric cerebral palsy

Abstract: Level IV retrospective therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…These results are comparable to those found in literature, with Cobb angle correction rates ranging from 54 to 82% and pelvic obliquity correction rate ranging from 42 to 86.8%, using Luque Galveston or Unit Rod instrumentation [25, 2932]. …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are comparable to those found in literature, with Cobb angle correction rates ranging from 54 to 82% and pelvic obliquity correction rate ranging from 42 to 86.8%, using Luque Galveston or Unit Rod instrumentation [25, 2932]. …”
Section: Discussionsupporting
confidence: 89%
“…Respiratory complications are a major concern in these patients, occurring in 23.5 to 57% of cases [21, 29, 45]. The analysis of our series found respiratory complications in only 15.6% of the population.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We investigated the individual studies to discern plausible explanations for the observed results. Nectoux et al [64] suggest that their spastic and non-ambulatory CP patients had increased risk of fractures with instrumented surgery. Phillips et al [46] reported implant breakages with two types of spino-pelvic anchorages.…”
Section: Implant-related Complicationsmentioning
confidence: 99%
“…Unit rods are additionally pre-shaped in three dimensions with kyphosis, lordosis, and pelvic portions to simplify their insertion. The correction of pelvic obliquity associated with this implant ranges from 57.8 % to 86 % at longest follow-up in retrospective series with pseudarthrosis affecting 0 to 5.9 % of patients [29,40,61,[64][65][66].…”
Section: Galveston Techniquementioning
confidence: 99%